Technology of Long-Distance Draining Goaf Water Under the Condition of Repeated Mining - LI Xiaolong, MU Pengfei (Meikuang Anquan, 2020)
Based on the example of goaf water drainage in the main transportation roadway of Hanzui Coal Mine, the formation of goaf water in the main transportation roadway is deeply analyzed. The conventional borehole B5 with the largest water inflow is selected as the target. It is suggested that the goaf water should be drained by a long directional borehole with long downward slope and upward elevation. The results show that the downward inclined and upward directional long borehole is suitable for long distance drainage of goaf water, and the drilling trajectory is designed as casing section, straight hole section, inclined section, stable inclined section, inclined section and stable inclined section, which can realize large angle oblique penetration through the old empty area. And avoiding the formation of drainage grooves, adopting directional drilling technology of clear water medium to ensure the straightness of casing section, stable directional drilling can be realized in 2 m to 7 m sand and mudstone interbedding below coal floor, and rotary drilling tool assembly is adopted. With the parameters of low drilling pressure and low torque, the smooth drilling in the old empty area can be realized, and finally the target area can be successfully drilled, and the good achievement of drilling 17 m in the old empty area and water inflow up to 134 m3/h after drilling can be realized. A total of 36 000 m3 of goaf water was released.